The relationship between air pollutants and COVID-19 cases and its implications for air quality in Jakarta, Indonesia - Muhammad Rendana; Leily Nurul Komariah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
World Health Organization (WHO) has announced that COVID-19 as a global pandemic and public health emergency. Previous studies have revealed that COVID-19 was an infectious disease and it could remain viable in ambient air for hours. Therefore, this study aims to examine the correlation between air pollutants (PM2.5, PM10, CO, SO2, NO2 and O3) and COVID-19 spread in Jakarta, Indonesia. Furthermore, this study also evaluates the impact of large-scale social restriction (LSSR) on air pollution index (API). Result of study found that air pollution index of PM2.5, PM10, CO, SO2 and NO2 decreased by 9.48%, 15.74%, 29.17%, 6.26% and 18.34% during LSSR period. While, for O3 showed an increase by 4.06%. Another result also found significantly positive correlations of SO2, CO and PM2.5 with COVID-19 cases. An exposure to SO2, CO and PM2.5 has driven the area become vulnerable for COVID-19 infection. Our findings indicated that the relationship between air pollutants and COVID-19 spread could provide a new notion for precaution and control method of COVID-19 outbreak.